2009
DOI: 10.1002/j.0022-0337.2009.73.1.tb04642.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Dental Students’ Attitudes About Older Adults

Abstract: Our study considered dental students' general attitudes towards older persons using the Aging Semantic Differential. The influence of age, gender, cohort, education, and academic exposure on general attitudes towards older adults was evaluated using a total of 328 dental students across all four years of academic standing. Students were assessed in the fall and spring semesters. The results showed differential responding on the four subscales, with slight positive ratings on the autonomy, acceptability, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 35 publications
8
60
0
Order By: Relevance
“…Another study on attitudes of Turkish medical and nursing students found a score quite close to our result (Total Mean KAOP score: 126.9) (Ayoğlu et al, 2013). In parallel with our research, it was determined that health care professionals or students had slightly positive attitude towards the elderly in studies performed in countries such as Sweden (Soderhamn et al, 2001), Jordan (Hweidi and Al-Obeisat, 2006), The U.S. (Nochajski, et al, 2009), Taiwan (Wang et al, 2009), China (Yen et al, 2009), Italy (Matarese et al, 2013), and Malawi (Zverev, 2013). The similar attitude findings towards the elderly that were obtained from different cultures can be explained as one of the effects of economic, social and cultural changes such as nations becoming closer together and similarity of cultural life that occurred during globalization.…”
Section: Discussionsupporting
confidence: 88%
“…Another study on attitudes of Turkish medical and nursing students found a score quite close to our result (Total Mean KAOP score: 126.9) (Ayoğlu et al, 2013). In parallel with our research, it was determined that health care professionals or students had slightly positive attitude towards the elderly in studies performed in countries such as Sweden (Soderhamn et al, 2001), Jordan (Hweidi and Al-Obeisat, 2006), The U.S. (Nochajski, et al, 2009), Taiwan (Wang et al, 2009), China (Yen et al, 2009), Italy (Matarese et al, 2013), and Malawi (Zverev, 2013). The similar attitude findings towards the elderly that were obtained from different cultures can be explained as one of the effects of economic, social and cultural changes such as nations becoming closer together and similarity of cultural life that occurred during globalization.…”
Section: Discussionsupporting
confidence: 88%
“…Didactic lectures were often included with other teaching approaches, such as experiential learning, discussion seminars, problem‐based learning, and community‐based rotations . Scenario‐ and problem‐based learning that use simulations of situations and case studies, respectively, were used to address various topics of interest .…”
Section: Resultsmentioning
confidence: 99%
“…This definition of school environment is also expanded to include exposure of students through externships and community experiences . Another study discussed the stressful school environment perpetrated by a heavy curriculum and how this affects students’ empathy levels, which already undergo a natural decrease throughout dental school …”
Section: Resultsmentioning
confidence: 99%
“…29 Furthermore Nochajski et al showed that in general, dental students displayed a modestly positive attitude towards older adults in three of the four scales (Integrity, Autonomy, Acceptability) and a relatively more negative attitude in the fourth (Instrumentality). 30 However, the findings of an investigation in Belgium showed that the attitude of recently graduated dentists towards the institutionalized elderly people was rather negative. 25 On the other hand, Sadaf & Yazdanie showed that the dental students' attitudes were very positive towards elderly patients and they showed a strong desire to treat them.…”
Section: Researchmentioning
confidence: 99%